The DNA-based Lassa vaccine INO-4500 confers durable protective efficacy in cynomolgus macaques against lethal Lassa fever - Viviane M. Andrade; Kathleen Cashman; Kyle Rosenke; Eric Wilkinson; Nicole Josleyn; Ginger Lynn; Jesse Steffens; Sean Vantongeren; Jay Wells; Connie Schmaljohn; Paul Facemire; Jingjing Jiang; et al. (Communications Medicine)
Abstract Background We have previously developed a DNA-based vaccine, INO-4500, encoding the Lassa lineage IV glycoprotein precursor. INO-4500, when delivered with electroporation, elicited humoral and cellular responses, and conferred 100% protection in cynomolgus non-human primates. Here, we expanded the characterization of INO-4500 assessing immunogenicity and protective efficacy of lower doses and single immunization, and the durability of immune responses. Methods The study was divided into three arms evaluating INO-4500 vaccination: Arm 1 – Dosing regimen; Arm 2 – Single immunization; and Arm 3—Durability of immune responses and protective efficacy. Humoral and T cell responses were assessed by IgG binding ELISA, IFNγ ELISpot and flow cytometry-based T cell activation assays. NHPs were challenged with a lethal dose of Lassa lineage IV 8 weeks (Arms 1 and 2) or one year (Arm 3) after immunization. NHPs were assigned clinical scores and monitored for survival. Viremia, virus neutralization and release of soluble mediators were assessed post-challenge, as well as disease pathology following NHPs death or euthanasia. Results INO-4500 induces dose-dependent immune responses and protective efficacy. Animals receiving two doses of 2 mg of INO-4500 show complete short- and long-term LASV protection. NHPs receiving 1 mg of INO-4500 are protected from LASV challenge one year after vaccination but are only partially protected 8 weeks post-vaccination. LASV-specific memory T cells are present in vaccinated NHPs one year after vaccination. INO-4500 vaccination prevents NHPs from developing severe disease. Conclusions These studies demonstrate that INO-4500 can provide short- and long-term protection in NHPs from lethal LASV challenge.